1982
DOI: 10.1590/s0004-282x1982000100008
|View full text |Cite
|
Sign up to set email alerts
|

Ação de corticoides na fase aguda da neurocisticercose: nota preliminar

Abstract: Neurocysticercosis is a major public health problem in the developing countries. Previous to the CT scan era its diagnosis was very restricted and conventional diagnostic methods were unreliable. It was also frequently necessary to submit patients to costly and dangerous surgical procedures to confirm the precise nature of the disease. The most striking type of neurocysticercosis diagnosed by CT is the acute or edematous type (Table 1). Patients with this type of neurocysticercosis are referred for examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…As it was described in literature, NC tends to take from 23 months to 7 years to calcify [7], it was demonstrated that in our sample the process was an accelerated one. In spite of the fact that treatment with anticyrcotic drugs does not extinguish the parasite, completely, from the CNS, in many cases, it can accelerate the calcification process [8][9][10][11][12][13][14][15][16][17][18][19][20]. As the CT findings at stage IV were statistically significant in relation to the normal neurological exam, we believe that the patients have been benefited by the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As it was described in literature, NC tends to take from 23 months to 7 years to calcify [7], it was demonstrated that in our sample the process was an accelerated one. In spite of the fact that treatment with anticyrcotic drugs does not extinguish the parasite, completely, from the CNS, in many cases, it can accelerate the calcification process [8][9][10][11][12][13][14][15][16][17][18][19][20]. As the CT findings at stage IV were statistically significant in relation to the normal neurological exam, we believe that the patients have been benefited by the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, Corral et al descreveram o primeiro caso de tratamento conservador, usando albendazol (15 mg/Kg/dia por 75 dias) e dexametazona (12 mg/Kg/dia por mais de 90 dias), com resolução completa da lesão cervical à RNM e recuperação dos déficits motores e sensitivos 1 . Portanto, o diagnóstico pré-operatório de CI pode ser importante, tendo em vista a possibilidade de tratamento medicamentoso 1,[11][12][13] . No futuro, com o avanço da técnicas de neuroimagem, o diagnóstico pré-operatório poderá ser feito mais frequentemente 2 .…”
Section: Fig 3 Estudo Histológico Mostrando Membrana Envoltória Conunclassified